Key Performance Indicator for Intrinsic Motivation in Micro, Small and Medium Enterprises (MSMEs) in Padang City - Mulyadi, Olandari; Karlinda, Ai Elis; Sari, Desi Permata (International Ecsis Association, 2025)
This study addresses the gap between the conceptual frameworks of Key Performance Indicators (KPIs) and their practical implementation in Micro, Small, and Medium Enterprises (MSMEs). While KPIs are widely adopted in large corporations as strategic performance measurement tools, their application in MSMEs remains inconsistent and underexplored, particularly in relation to owners’ intrinsic motivation. This research analyzes how KPI implementation influences the intrinsic motivation of MSME owners in Padang City through a quantitative approach involving 100 respondents. The results showed that the simultaneous application of KPI had a significant effect on intrinsic motivation, as shown by the test value of F (15.961; Sig. 0.000). The value of the determination coefficient (R² = 0.459) indicates that 45.9% of the variation in intrinsic motivation is explained by five KPI methods: BSC, SMART, Benchmarking, Participatory Approach, and Data Analytics. However, the results of the partial test showed that only Data Analytics had a significant effect on intrinsic motivation, while the other methods had no effect. These findings confirm that MSME owners are more driven by the practical and evidence-based implementation of KPIs, especially through data analysis, rather than conceptual frameworks. The novelty of this research lies in the emphasis on data analytics-based KPIs as a determinant of intrinsic motivation of MSME owners. This research provides a theoretical contribution by expanding the MSME performance management literature as well as practical contributions in the form of recommendations for MSME owners in strengthening intrinsic motivation and ensuring the long-term sustainability of MSMEs.